Apakah Kegiatan Sosial Bank Syariah Meningkatkan Kesejahteraan Masyarakat? - Nofinawati, Nofinawati; Sudiarti, Sri; Marliyah, Marliyah; Nasution, Adanan Murroh (Universitas Islam Negeri Alauddin Makassar, 2024)
This study was conducted to describe the implementation of social activities of Islamic banks and to describe the impact of social activities on community welfare in Padangsidimpuan City. The phenomenon that made the author interested in studying this problem is the low number of implementations of social products in Islamic banks. This can be seen from the number of fund distributions using the Qardh contract which is less when compared to other contracts. This will certainly have an impact on the welfare of the community around the operational area of ​​the Islamic bank. The author uses field research, qualitative methods with descriptive analysis. The implementation of social activities by Islamic banks in Padangsidimpuan City shows a strong commitment to community welfare, with various programs such as collecting and distributing zakat funds, qardhul hasan, educational scholarships, and responding to natural disasters. These activities have a positive impact in reducing economic pressure on the community and creating a sense of solidarity. However, these positive impacts tend to be temporary, and there are challenges faced in the management and distribution of aid. Limited authority in distributing social funds, strict aid requirements, and lack of effective communication are obstacles that must be overcome to increase the effectiveness of social activities. From the research results, it is seen that although Islamic banks are trying to carry out their social functions well, they need to pay attention to and overcome existing challenges so that these programs can provide more sustainable benefits to the community. This includes developing strategies that are more inclusive and responsive to community needs. Increasing transparency in the aid distribution process and active community participation are also very important to create trust and reduce dissatisfaction.